Identification of two glycerophosphodiester phosphodiesterase genes in maize leaf phosphorus remobilization - Jingxin Wang; Wenbo Pan; Alexiy Nikiforov; William King; Wanting Hong; Weiwei Li; Yang Han; Jana Patton-Vogt; Jianbo Shen; Lingyun Cheng (Crop Journal, 2021)
Phosphate deficiency is one of the leading causes of crop productivity loss. Phospholipid degradation liberates phosphate to cope with phosphate deficiency. Glycerophosphodiester phosphodiesterases (GPX-PDEs) hydrolyse the intermediate products of phospholipid catabolism glycerophosphodiesters into glycerol-3-phosphate, a precursor of phosphate. However, the function of GPX-PDEs in phosphate remobilization in maize remains unclear. In the present study, we characterized two phosphate deficiency-inducible GPX-PDE genes, ZmGPX-PDE1 and ZmGPX-PDE5, in maize leaves. ZmGPX-PDE1 and ZmGPX-PDE5 were transcriptionally regulated by ZmPHR1, a well-described phosphate starvation-responsive transcription factor of the MYB family. Complementation of the yeast GPX-PDE mutant gde1∆ indicated that ZmGPX-PDE1 and ZmGPX-PDE5 functioned as GPX-PDEs, suggesting their roles in phosphate recycling from glycerophosphodiesters. In vitro enzyme assays showed that ZmGPX-PDE1 and ZmGPX-PDE5 catalysed glycerophosphodiester degradation with different substrate preferences for glycerophosphoinositol and glycerophosphocholine, respectively. ZmGPX-PDE1 was upregulated during leaf senescence, and more remarkably, loss of ZmGPX-PDE1 in maize compromised the remobilization of phosphorus from senescing leaves to young leaves, resulting in a stay-green phenotype under phosphate starvation. These results suggest that ZmGPX-PDE1 catalyses the degradation of glycerophosphodiesters in maize, promoting phosphate recycling from senescing leaves to new leaves. This mechanism is crucial for improving phosphorus utilization efficiency in crops.